Cutaneous Allergic reactions to pine processionary caterpillar (Thaumetopoea Pityocampa): a complicated cutaneous reaction in an infant and review of the literature - Galip, Nilüfer; Şanlıdağ, Burçin; Babayiğit, Arzu; Bahçeciler, Nerin Nadir (The Turkish Journal of Pediatrics, 2022)
Background. Thaumetopoea Pityocampa (TP) are frequent in the Mediterranean region especially affecting forest workers in pinewood areas. The common symptoms include swelling, rash or burns like any form of dermatitis. The reactions can be triggered by mechanical, chemical or allergic factors and the `allergic` reaction is caused by sensitization to a hair protein named `thaumetopoein`. This protein triggers the IgE mediated reaction resulting in the mast cell degranulation causing urticaria. Different kinds of allergic reactions like urticaria or anaphylaxis have been reported previously commonly in adults, especially in forest workers while severe reactions without direct contact are rare in pediatric population. Case. A 28 month old healthy boy was admitted to Near East University Pediatric Allergy and Immunology Outpatient Clinic in March with complaints of pain, hyperemia and swelling on the left hand. His complaints had started the day before his admission just after walking around in their garden which is surrounded by pine trees. On admission, his physical examination revealed serious edema and hyperemia on his left hand limiting his finger movements with a few bullae on the skin. His temperature was 38 C and the other vital parameters were normal. Based on hyperemia, swelling and high acute phase reactants he was hospitalized with the differential diagnosis of soft tissue inflammation and cellulitis. The case was treated with iv antihistamines, systemic steroids and antibiotics. Conclusions. Pine processionary (PP) is an important irritant and allergen especially in endemic areas like Cyprus which is a Mediterranean Country. It must be kept in mind in case of local or generalized urticaria, dermatitis, bullae and other allergic reactions even if there had been no direct contact with PP. Systemic involvement with fever and elevated acute phase reactants in infancy may necessitate hospitalization and intravenous treatment. Hereby, we reported an infant who presented with fever in addition to severe cutaneous lesions following the exposure to TP without direct contact. This is the first case reported from North Cyprus.